2017
DOI: 10.1002/gch2.201700066
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Photonic Efficiency of Novel Photocatalytic Niobium Oxide Materials

Abstract: The application of niobium oxides as photocatalytic materials for the removal of contaminants is scarcely reported in the literature. This work reports the methodology to synthesize four different mesoporous niobium oxide materials and the correlation between the physicochemical properties and the photocatalytic activity. X‐ray diffraction, UV–vis diffuse reflectance spectra (DRS), transmission electron microscopy, and nitrogen adsorption techniques are used to characterize the structure and composition of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…By analyzing the diffractograms, it is possible to verify that the catalyst 1.0% Fe/Nb 2 O 5 , 0.5% Fe/Nb 2 O 5 , and 1.5% Fe/Nb 2 O 5 samples calcined at 673K have a non-crystalline (amorphous) structure. Similar results were found for niobium samples at the same catalyst calcination temperatures from research conducted by Morais et al (2017) [26]. The diffractograms indicate that the TT-Nb 2 O 5 (ICDD00-028-0317) with the cell parameters a = b = 3.6070 Å, c = 3.9250 Å, and T-Nb 2 O 5 (ICDD00-027-1313) forms with the cell parameters a = 6.1680 Å, b = 29.3120 Å, and c = 3.9380 Å were obtained for the catalysts calcined at temperatures higher than 673 K. It was also observed that 1.0% Fe/Nb 2 O 5 , 1.7% Fe/Nb 2 O 5 calcined at 773 K and 0.5% Fe/Nb 2 O 5 , 1.5% Fe/Nb 2 O 5 calcined at 873 K and 1.0% Fe/Nb 2 O 5 calcined at 913 K showed a semi-crystalline structure, with crystallite sizes of 30,26,35,35, and 40 nm, respectively.…”
Section: Pore Properties (Bet Method)supporting
confidence: 84%
“…By analyzing the diffractograms, it is possible to verify that the catalyst 1.0% Fe/Nb 2 O 5 , 0.5% Fe/Nb 2 O 5 , and 1.5% Fe/Nb 2 O 5 samples calcined at 673K have a non-crystalline (amorphous) structure. Similar results were found for niobium samples at the same catalyst calcination temperatures from research conducted by Morais et al (2017) [26]. The diffractograms indicate that the TT-Nb 2 O 5 (ICDD00-028-0317) with the cell parameters a = b = 3.6070 Å, c = 3.9250 Å, and T-Nb 2 O 5 (ICDD00-027-1313) forms with the cell parameters a = 6.1680 Å, b = 29.3120 Å, and c = 3.9380 Å were obtained for the catalysts calcined at temperatures higher than 673 K. It was also observed that 1.0% Fe/Nb 2 O 5 , 1.7% Fe/Nb 2 O 5 calcined at 773 K and 0.5% Fe/Nb 2 O 5 , 1.5% Fe/Nb 2 O 5 calcined at 873 K and 1.0% Fe/Nb 2 O 5 calcined at 913 K showed a semi-crystalline structure, with crystallite sizes of 30,26,35,35, and 40 nm, respectively.…”
Section: Pore Properties (Bet Method)supporting
confidence: 84%
“…Nb 2 O 5 and Ni/Nb 2 O 5 materials exhibit a type II isotherm with an H3 hysteresis (Thommes et al., 2015), corroborating the non-structural porosity created by the packing of Nb 2 O 5 nanorods. Niobium oxide nanoparticles can be obtained by various synthesis methods, which leads to the preparation of materials of different shapes with Brunauer-Emmett-Teller (BET) specific surface areas that can range from about 20 m 2 g −1 to 530 m 2 g −1 (Luisa Marin et al., 2014, Morais et al., 2017, Shao et al., 2017). Table 1 shows the as-synthesized Nb 2 O 5 support to possess a relatively high specific surface area (196 m 2 g −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Following the literature, the observed components may be associated with the O 2− →Mn 2+ , O 2− →Mn 3+ , and O 2− →Mn 4+ charge transfer transitions along with a mixture of the Mn d-d transitions in the partially distorted octahedral crystal field of the cryptomelane framework [37][38][39][40][41]. Due to a possible overlapping of the absorption bands below 400 nm [42,43], it is rather difficult to identify any characteristic features in the recorded spectra attributable to the presence of niobia or niobates. However, it is apparent that the positions and relative intensities of the observed bands are influenced by the Nb presence.…”
Section: Chemical Composition and Manganese Redox State Analysismentioning
confidence: 60%